The plays to 1942 : Mulatto to The sun do move - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Collected works of Langston Hughes, 2002)
But someday somebody'll Stand up and talk about me - Black and beautiful - And sing about me. And put on plays about me! I reckon it'll be Me myself! Yes, it'll be me. Langston Hughes is least known for his theatrical endeavors, yet his attention to the theater was lifelong. His love of the stage began in childhood, and from the late 1920s on he was continually writing plays, for black community theater, for theater companies he established himself, and for the Broadway and off-Broadway stage. His early plays endeavor to provide "authentic" representations of African American life, both to counter and correct the stereotypical stage portrayals of African Americans in white theater and to provide suitable plays for black theater companies hungry for scripts that would entertain and challenge black audiences. Volume 5 of The Collected Works of Langston Hughes includes the plays Hughes wrote between 1930 and 1942, alone and in collaboration. Almost all the plays were performed during the same period; a few have never seen the stage, but are included because they indicate the range of Hughes's artistic and political concerns. Because very few of the plays in this volume have been previously published, they disclose a side of Langston Hughes's artistry that is virtually unknown. The collection greatly expands our understanding of the Hughes legacy, and makes us rethink the history of African American theater